McCosker Bore Camp, telephone booths, 4 August, 2002 - Van Lit, Anya, 1968- (2002)
"Telstra has the tender for telecommunication of the project and provides here telephone facilities for the workers in the camp. This camp has to relay on satellite telephones."--Description supplied by photographer, see file NLA/14137.
Part of collection: Alice Springs to Darwin Railway construction, Northern Territory, 1-6 August, 2002.
Title supplied by photographer.
Also available online
Keywords: Telephone booths -- Northern Territory -- Photographs; Camp sites, facilities, etc. -- Northern Territory -- Photographs